Extraction of a trapped pacemaker lead in a pacemaker-dependent patient - Kypta, Alexander (J Cardiol Cases, 2015)
A 47-year-old female with a dual chamber pacemaker was referred to our institution for transvenous lead removal because of suspected pocket infection. The history of this patient started in 2002 with a tricuspid valve endocarditis. Therefore, the patient had tricuspid valve repair that yielded a poor outcome. The patient received biological tricuspid valve in 2006. Due to postoperative total atrioventricular-block a DDDR device was implanted. The biological valve degenerated and thus was replaced by a mechanical one in 2014. During this valve implantation the atrial lead was removed and the ventricular lead was trapped by the mechanical valve between the native tricuspid valve annulus of the right ventricle and the outer ring of the mechanical valve. Three months after the last revision the patient developed signs of inflammation. The pocket was opened and a swab test proved positive for Staphylococcus epidermidis. After disinfection with iodine solution the pacemaker was placed under the pectoralis muscle. However, during the following 3 months the patient suffered from swelling over the pacemaker pocket and severe pain. In awareness of the previous history and the clinical symptoms we decided to implant a new pacemaker system on the left side and explant the infected system on the right side. <Learning objective: Pocket infections always require system explantation. Simultaneous explantation of an infected system and implantation of a new system within the same session is not recommended but was necessary in this case. Even complex lead extraction like this one can be successfully performed applying the appropriate tools (locking stylet, Evolution device, Cook Intravascular Inc., Leechburg, PA, USA).>